Agricultural Innovation and the Protection of Traditional Rice Varieties: Kerala a Case Study - Blakeney, Michael; Krishnankutty, Jayasree; Raju, Rajesh K.; Siddique, Kadambot H. M. (Frontiers in Sustainable Food Systems, 2020)
In an endeavor to promote agricultural innovation, the Government of India introduced two pieces of legislation: (i) the Protection of Plant Varieties and Farmers' Rights Act, 2001, which provide for the registration of traditional crop varieties as farmers' varieties, and for the sharing of benefits when those varieties are incorporated into new commercial varieties; and (ii) the Geographical Indications of Goods (Registration and Protection) Act 1999, which provides for the registration of indications to promote the marketing of goods which derive their quality and characteristics from their geographical origin. This article tests the effectiveness of this legislation in promoting agricultural innovation, reporting on a survey of 401 farmers of traditional rice varieties in Kerala, South West India. The study revealed that farmers were either unaware of the legislation, or unaware of its functions. They have not been much involved in the registration of farmers' varieties and have not made any benefit-sharing claims in relation to the varieties which have been registered. They have tended to confuse the registration of geographical indications with the registration of farmers' varieties. This suggests, as a first step, the necessity for awareness raising about the purposes of both pieces of legislation with Indian farmers.